2011
DOI: 10.4319/lo.2012.57.1.0058
|View full text |Cite
|
Sign up to set email alerts
|

Fight and flight in dinoflagellates? Kinetics of simultaneous grazer‐induced responses in Alexandrium tamarense

Abstract: We monitored the kinetics of grazer-induced responses in the marine dinoflagellate Alexandrium tamarense. Chemical cues from each of three calanoid copepods (Calanus sp., Centropages typicus, and Acartia tonsa) induced increased toxicity and suppressed chain formation in A. tamarense. Both chemical and morphological responses augmented over 3 d. Toxicity subsequently averaged 299% higher than controls, and average biovolume 24% lower than controls because of suppression of chain formation in grazed treatments.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 21 publications
2
35
0
Order By: Relevance
“…(Selander et al, 2006), but the full induction takes 2-4 days (Selander et al, 2012), and is low with the low concentration of copepods used here (1 per 800 ml). Thus, it is assumed that the chemical profile of cells from the culture is representative for the experiments.…”
Section: Copepod Feeding Behaviormentioning
confidence: 88%
“…(Selander et al, 2006), but the full induction takes 2-4 days (Selander et al, 2012), and is low with the low concentration of copepods used here (1 per 800 ml). Thus, it is assumed that the chemical profile of cells from the culture is representative for the experiments.…”
Section: Copepod Feeding Behaviormentioning
confidence: 88%
“…In the present study, no costs of producing DA were observed, as there were no differences in growth rates between the highly toxic and the less toxic cells. However, there may be indirect costs that could not be detected in the batch cultures, as suggested by Bergkvist et al (2008) and Selander et al (2012) for the PST-producers A. minutum and A. tamarense, respectively. In the field, DA production is likely to be controlled by several interacting factors, which makes it difficult to predict the formation of a toxic bloom.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the first study to address induction of DA production in Pseudo-nitzschia species by zooplankton. Given that other studies have shown toxin production in other algal groups can be induced by chemical cues from zooplankton (Jang et al, 2003;Selander et al, 2006Selander et al, , 2012, this possibility should be investigated more rigorously with other Pseudo-nitzschia species and zooplankton.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that attaining a single-or double-cell modus is an advantageous adaptation for S. marinoi populations developing in environments with abundant copepod grazers. The marine dinoflagellate Alexandrium tamarense responds to grazer cues with simultaneous reduction in chain length, swimming speed, and increased toxicity (Selander et al 2011;Selander et al 2012). The lower grazing rates on grazer-induced Skeletonema cells could therefore have resulted from other defense mechanisms correlated to the changes in chain length.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, while Jakobsen and Tang (2002) found that colony formation in Phaeocystis globosa increased when grazed by the heterotrophic dinoflagellate Gyrodinium dominans, Long and colleagues (Long et al 2007) found that P. globosa suppressed colony formation by 60-90% in response to cues from grazing copepods. The dinoflagellate Alexandrium tamarense splits up chains and reduces swimming speed in response to grazer cues, which reduces grazer encounter rates severalfold (Selander et al 2011). Dominant copepod grazers are typically omnivorous (Turner 2004), and ideally any defensive mechanism should not aim to reduce grazer abundances per se because co-occurring, competing phytoplankton would benefit equally.…”
Section: Discussionmentioning
confidence: 99%